Metode Pembelajaran Bahasa Arab untuk Anak Usia Dini Berbasis Fun-Based Learning - Nurul Fitria Aprilia; Hanifa Hafiza; Malikatus Sholihah (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This research discusses about examines the application of Fun-Based Learning in teaching Arabic to early childhood students at KB Bina Anak Muslim. Through observations, interviews, and documentation, it was found that the program incorporates varied methods such as singing, playing, memorization, and writing, aligning with the developmental needs of young children. The primary teaching resource is the Hijaiyah book, supplemented with diverse learning media, including flashcards, electronic devices, and coloring worksheets. The learning process is structured into distinct stages: opening (prayer and topic discussion), questioning (simple Q&A), main activities (reciting and coloring Hijaiyah letters), break time, and closing (vocabulary review and daily prayers). Documentation reveals the effectiveness of combining these methods and media in creating an engaging and effective learning environment, fostering children's enthusiasm for learning Arabic. The integration of these various approaches supports early childhood cognitive, social, and emotional development, making Arabic language learning accessible and enjoyable.